Trends in the training of university teachers who work in our visual arts courses (Brazil and Argentina) (Palíndromo, 2022)
In this article, we present the trends in initial (Graduate) and continuing (Post-Graduation stricto sensu) training of university professors (trainers) who work in Undergraduate courses in Visual Arts in Brazil and Argentina. The research is the result of the author’s doctoral thesis, defended in 2020 at the PPGAV/ UDESC. The selected professors come from 23 public Higher Education Institutions (HEIs) that offer undergraduate courses in Visual Arts in the on-site modality (10 in Argentina and 13 in Brazil), making up a total of 604 professionals (324 in Argentina and 280 in Brazil). We found consonant and dissonant aspects regarding training trends and requirements for Higher Education in both countries. The similarities consist of the areas of initial and continuing education, as well as artistic production or not according to the three disciplinary axes (artistic/studio, theoretical/historical and pedagogical/teaching) of the teachers’ performance, and the maximum degree and the laws that regulate the teaching profession in higher education in both countries.
Keywords: Visual arts; College professor; Trainer training; Brazil and Argentina; OFPEA/BRARG